Pediatric dentistry post coronavirus disease 2019: Changing treatment paradigms in the pandemic setting - M M Dempsy Chengappa; Atul Bali; Rahul Kaul; Rishu Koul (Wolters Kluwer Medknow Publications, 2022)
Coronavirus disease 2019 (COVID-19) pandemic has had a great impact on the practice of dentistry. Dental setups are potential focal points for cross-infection, and utmost care must be taken to reduce the risk of infection to, from, or among dentists, paradental staff, and patients. A specific concern for children is the uncertainty of their infection status; a clinical history may not be as suggestive of the infection as it is in adults. This makes pediatric dentists more prone to getting infected by the disease. The present review is aimed to provide an overview of potential dental emergencies in pediatric dental practice and a summary of the available treatment strategies that can be utilized by pediatric dentists with an aim to minimize aerosol generation to reduce chances of transmission during and after COVID-19 pandemic.